Micro/nano engineering on stainless steel substrates to produce superhydrophobic surfaces - Beckford, Samuel; Zou, Min (Thin solid films, 2011)
Creating micro-/nano-scale topography on material surfaces to change their wetting properties has been a subject of much interest in recent years . Wenzel in 1936 and Cassie and Baxter in 1944 proposed that by microscopically increasing the surface roughness of a substrate, it is possible to increase its hydrophobicity. This paper reports the fabrication of micro-textured surfaces and nano-textured surfaces, and the combination of both on stainless steel substrates by sandblasting, thermal evaporation of aluminum, and aluminum-induced crystallization (AIC) of amorphous silicon (a-Si). Meanwhile, fluorinated carbon films were used to change the chemical composition of the surfaces to render the surfaces more hydrophobic. These surface modifications were investigated to create superhydrophobic surfaces on stainless steel substrates. The topography resulting from these surface modifications was analyzed by scanning electron microscopy and surface profilometry. The wetting properties of these surfaces were characterized by water contact angle measurement. The results of this study show that superhydrophobic surfaces can be produced by either micro-scale surface texturing or nano-scale surface texturing, or the combination of both, after fluorinated carbon film deposition.